Great Tits Build Shallower Nests than Blue Tits in an Insular Oak-Dominated Habitat Mosaic. (June 2015) - Lambrechts, Marcel M.; Blondel, Jacques; Dubuc-Messier, Gabrielle; Marrot, Pascal; de Franceschi, Christophe; Perret, Philippe; Doutrelant, Claire; Grégoire, Arnaud; Charmantier, Anne
Longitudinal multi-plot studies of nest architecture in non-domesticated birds are rare. Here we report the results of an 18-year multi-plot study that compared heights of fresh female-built nests in Corsican Great Tits ( Parus major ) and Blue Tits ( Cyanistes caeruleus ogliastrae ). Boxes with relatively small nest-chambers were erected in a landscape with habitat patches that were either dominated by food-rich broad-leaved deciduous oaks ( Quercus humilis ) or food-poor evergreen oaks ( Quercus ilex ). Nest height tended to change with oak habitat type in a species-specific manner. Great Tits built shallower nests than Blue Tits supporting the published findings from other geographic regions (Poland, UK, southern mainland France). Potential impacts of local climate factors and risks related to nest predation on the species-specific expression of the size of nests are discussed.